2011
DOI: 10.1016/j.diagmicrobio.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Pneumocystis jirovecii in lungs from colonized COPD patients

Abstract: Pneumocystis jirovecii has been detected in lung tissue from patients with chronic obstructive pulmonary disease (COPD) and is associated with disease severity. The regional distribution of the organism in lungs is unknown, but differences in distribution of Pneumocystis could affect estimates of colonization prevalence. We examined the distribution of Pneumocystis in the lungs of 19 non-HIV-infected patients with COPD who were undergoing lung transplantation. DNA was extracted from explanted lungs. We found P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
1
21
0
2
Order By: Relevance
“…Despite technical factors that can influence the reported prevalence of Pneumocystis colonization, and according to the abovecited studies (including our results), it appears that CF is associated with lower Pneumocystis colonization rates than are other chronic pulmonary diseases (14,20,22,24,26,27,32). Three studies have reported the association of P. jirovecii and P. aeruginosa in CF patients (14,22,25), but whether Pneumocystis infection/colonization complicated CF-associated lung disease remains unclear.…”
supporting
confidence: 45%
“…Despite technical factors that can influence the reported prevalence of Pneumocystis colonization, and according to the abovecited studies (including our results), it appears that CF is associated with lower Pneumocystis colonization rates than are other chronic pulmonary diseases (14,20,22,24,26,27,32). Three studies have reported the association of P. jirovecii and P. aeruginosa in CF patients (14,22,25), but whether Pneumocystis infection/colonization complicated CF-associated lung disease remains unclear.…”
supporting
confidence: 45%
“…Pneumocystis also infects patients receiving long-term immunomodulatory therapy for rheumatoid arthritis and other inflammatory diseases (4) as well as cancer patients undergoing chemotherapy (5). Furthermore, Pneumocystis infection or colonization has been associated with chronic obstructive pulmonary disease in both HIV and non-HIV patients (6).…”
mentioning
confidence: 99%
“…The host's immune response against this pathogen often contributes to severe PcP-related lung injury (6,7). Clinical studies suggest that the intensity of pulmonary inflammation, rather than organism lung burden, correlates with the severity of PcP (8)(9)(10).…”
mentioning
confidence: 99%
“…Although the mechanism(s) for this is unknown, it has been hypothesized that subclinical pulmonary infections could be involved. In turn, the atypical fungal organism Pneumocystis jirovecii is increasingly becoming associated with COPD in both non-HIV and HIV patients (26,27,36). We have recently determined that HIV-positive individuals colonized with Pneumocystis had worse airway obstruction in the presence of higher levels of MMP12, but not MMP1, MMP2, or MMP9, in sputum compared with noncolonized HIV-positive individuals (25).…”
mentioning
confidence: 99%